Social Capital Development Model in the Coastal Ecosystem Conservation Strategy of Sibolga City and Central Tapanuli Regency, North Sumatra Province - Henry Sitorus; Hamdani Harahap (PT FORMOSA CENDEKIA GLOBAL, 2022)
Deep Ecology has already spread around of scholars as mainstream perspective and ethic in environment conservation system. Indeed, it is required as the specific strategy for the implementation coastal ecosystem conservation approach. Ihis research is aim to found some social capital aspect in coastal community i.e social trust degrees, collective consciences, social values and norms, networking of social institution that need for coastal ecosystem conservation strategy. Based on this research, some aspects of Tapian Nauli coastal ecosystem should be conducted by co-option of local government, communities, corporations, and social organization partnership role to apply social capital capacity manner which is significant to reduct the coastal ecosystem degradation as well as a conservation strategy in Kota Sibolga and Kabupaten Tapanuli Tengah.